'A Striking Air of Modernity Tempered with Tradition': Vernacular Modernism and the Design of the Public House in Cork and Dublin, 1934–1969. (13th January 2022) - Spalding, Tom
Abstract: In design history discourse, modernity and tradition can be seen as intimately related rather than dichotomous. For example, Michelangelo Sabatino has noted the complex relationship between them in Italian twentieth-century architecture. What was the relationship between modernity and tradition in post-Independence Ireland? One way of investigating this is to consider the design of a quintessentially everyday space: the pub. From the 1930s, many pubs in Cork and Dublin were re-designed through a series of negotiated responses to modernisation. By 1960, this was complicated by the construction of what we would recognize as interiors designed to appeal to an imagined tourist vision of the pub in Ireland. This article argues that these changes were design responses to three interlinked historical forces: modernization, the retention or invention of vernacular design, and the influence of international trade and tourism. This considerably complicates our understanding of Irish modernism and illustrates that, for the public house in Ireland at least, British design was a dominant influence.